3D chemical characterization of frozen hydrated hydrogels using ToF-SIMS with argon cluster sputter depth profiling - Taylor, Michael; Scurr, David; Lutolf, Matthias; Buttery, Lee D.K.; Zelzer, Mischa; Alexander, Morgan R. (American Vacuum Society, 2015)
Hydrogels have been used extensively in bioengineering as artificial cell culture supports. Investigation of the interrelationship between cellular response to the hydrogel and its chemistry ideally requires methods that allow characterization without labels and can map species in three dimensional to follow biomolecules adsorbed to, and absorbed into, the open structure before and during culture. Time-of-flight secondary ion mass spectrometry (ToF-SIMS) has the potential to be utilized for through thickness characterization of hydrogels. The authors have established a simple sample preparation procedure to successfully achieve analysis of frozen hydrated hydrogels using ToF-SIMS without the need for dry glove box entry equipment. They demonstrate this on a poly(2-hydroxyethyl methacrylate) (pHEMA) film where a model protein (lysozyme) is incorporated using two methods to demonstrate how protein distribution can be determined. A comparison of lysozyme incorporation is made between the situation where the protein is present in a polymer dip coating solution and where lysozyme is in an aqueous medium in which the film is incubated. It is shown that protonated water clusters H(H2O)nþ where n ¼ 5–11 that are indicative of ice are detected through the entire thickness of the pHEMA. The lysozyme distribution through the pHEMA hydrogel films can be determined using the intensity of a characteristic amino acid secondary ion fragment.